Pengaruh Pelatihan Komunikasi Efektif dalam Meningkatkan Efektivitas Tim - Huda Nur Aziz; Fuad Nashori; Faraz (Warta Pendidikan | e-Journal, 2020)
This research aimed to empirically observe the effects of effective communication in improving the team effectiveness. The hypothesis proposed in this research was that there was a difference in the effectiveness of respondent team before and after providing the effective communication training. The respondents involved in this research were thirteen employees that had the medium and low level of team effectiveness. This is a quasi-experiment research with one group pretest-posttest design. The variable of team effectiveness was measured using the scale adapted from the Daft’s theory of team effectiveness (2003), while the effectiveness communication was measured using the scale adapted from the Jalaluddin’s theory of effective communication (2008). The data analysis used was Paired Sample T Test using IBM SPSS Statistics for Mac. The results of the data analysis showed the difference in team effectiveness before and after the effective communication training. Once the effective communication training was given, there was a significant change in team effectiveness in PT CTU Malang.